Interdiscursivity of Biofictional Narration: the Image of Petersburg in M. Bradbury’s “To the Hermitage” - N. A. Urusova (Дискурс)
Introduction. The present paper deals with the interdiscursivity in postmodern literary biographic narration (biofiction) in which interdiscursivity is viewed as the author’s strategy of text formation. The relevance of the study is conditioned by the interest of modern linguistics in interaction of different discourse types in literary texts. It is also relevant to study different techniques that the English author uses to represent an external linguocultural context, namely, to create the image of a Russian city in the English-language narration. The novelty of the research is implied by the choice of material under examination, as the constitutive elements of biofictional narration have not been fully defined yet.Methodology and sources. The study is drawn on M. Bradbury’s English-language postmodern biofictional novel To the Hermitage. This biofiction depicts D. Diderot’s trip to St. Petersburg, where he was invited by Catherine the Great. It also recounts the adventures of a modern expedition, which came to the same destination to study the French philosopher’s heritage. The research of discourse interaction is based on a methodology, developed by V. Chernyavskaya. It combines traditional methods of stylistic analysis with discourse analysis.Results and discussion. While analysing the literary space of the biofiction, the following “central” discourses have been identified: Russian-culture-oriented discourse of English as well as historical, political, and autobiographical discourses. The narration is also rich in traits of “periphery” discourses, to name just a few: economical, literary, colloquial French, etc. M. Bradbury uses the strategy of simulated interdiscursivity to make a persuasive impact on a reader’s mind, at the same time involving the reader in fact-fiction semantic game.Conclusion. The analysis highlighted here proved the fact that interdiscursivity is one of the dominant mechanisms an author uses to construct biofictional narration. This strategy reflects some key features of postmodern texts, such as blending of literary genres, a playful montage of different discourse types and ironic mode of narration.